Kepemimpinan Kepala Sekolah Dalam Resiliensi Sekolah Di Era Digital - Wiyana, Adi; Hidayati, Dian; Suyata, Suyata; Hasanah, Enung (Universitas Muhammadiyah Surakarta, 2024)
In the digital era, the leadership of school principals necessitates serious consideration to act as a catalyst for teachers adapting to changes. Principals must be capable of addressing the various challenges of education and transforming problems into opportunities to establish schools, that yield high-quality graduates. They must also generate creative and innovative ideas in their leadership role. There are several leadership styles that principals can adopt in the digital era, including authoritarian, democratic, laissez-faire, transformational, transactional, and authoritarian styles. This research aims to comprehend and describe the various challenges principals face in the digital era. It employed a qualitative descriptive approach and interview methods and was conducted at SD Muhammadiyah Special Program Rabbani Karanganom, Klaten, Central Java. Interviews were conducted with the principal, ICT teachers, and a driving teacher. The research concludes that principals, as leaders, must confront various challenges in democratic and styles being the most dominant, in the digital era should provide comfort, with the democratic and transformational styles being the most dominant. Digital leaders in schools should embody four main characteristics: problem-solving, collaboration, a love for learning, and a student-focused approach.